Developments in the value of implicit guarantees for bank debt The role of resolution regimes and practices - Schich, Sebastian (OECD Publishing, 2013)
High values of implicit guarantees for bank debt can be taken as signalling the market's expectation that public authorities will rescue the institution in question in times of severe financial distress. By the same token, declines in the measure would suggest a drop in the perceived likelihood of such a bailout, perhaps reflecting the availability of more effective failure resolution tools (although they could also reflect other factors such an improvement in the asset quality of banks)